Double-crosslinking hydrogel based on E-PLMnO2 nano-enzyme as well as preparation method and application of double-crosslinking hydrogel
By using a double-cross-linked hydrogel material of guar gum and hyaluronic acid, combined with δ-MnO2 and ε-polylysine nanozymes, the problem of insufficient strength and stability of hydrogels in diabetic wound healing was solved, achieving efficient oxidative stress relief and antibacterial effects, and promoting wound healing.
Patent Information
- Application Number
- CN202510843605.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-23
- Publication Date
- 2025-10-10
AI Technical Summary
Existing hydrogel materials are difficult to simultaneously take into account strength, stability and wound healing effects in diabetic wound healing, and traditional cross-linking agents have toxicity risks and complex reaction conditions, making it difficult to meet the demand for green, non-toxic and environmentally friendly materials.
Using guar gum and hyaluronic acid as the base material, a double-crosslinked three-dimensional network structure was constructed through the synergistic action of borate bonds and hydrogen bonds, and EM nanozymes composed of δ-MnO2 and ε-polylysine were introduced to regulate oxidative stress levels and inhibit bacterial infection.
The hydrogel has achieved excellent stability and mechanical properties, significantly alleviated oxidative stress, inhibited inflammatory response, and promoted wound healing. It is suitable for on-site treatment of irregular wounds and postoperative wounds, providing continuous structural support and functional delivery.
Smart Images

Figure CN120754021A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to a double-crosslinked hydrogel based on E-PLMnO2 nanoszyme and a preparation method and application thereof, and belongs to the technical field of biomedical materials. BACKGROUND
[0002] Diabetic wound bacterial infection and hyperglycemia can lead to long-term high levels of oxidative stress and further cause serious complications, which is the biggest challenge in the research of diabetic wound healing. Wound dressings are considered an important wound healing material, and there are many different types, including gauze, film, foam or hydrogel, etc., which directly contact the wound, protect the wound from further injury or infection, and promote healing. Among these dressings, hydrogels are increasingly attracting attention as an ideal candidate for treating and protecting long-term inflammatory wounds.
[0003] The hydrogel system currently proposed by the research mainly achieves a multifunctional strategy to promote wound repair through the synergistic effect of various exogenous additives such as antibacterial agents, bioactive substances and growth factors, but at the same time faces problems such as drug resistance, high cost and complex preparation and production process. On the other hand, the performance of hydrogels depends on a single crosslinking method, making it difficult to meet the needs of long-term healing and chronic wound repair in clinical practice in terms of mechanical strength, degradation rate and other aspects. In addition, most commercial hydrogel materials use chemical crosslinking, and in some hydrogels, traditional chemical crosslinking agents can effectively enhance the stability of the gel, but also pose a potential risk of toxicity. In addition, the use of these crosslinking agents often requires complex reaction conditions, making it difficult to meet the demand for green, non-toxic and environmentally friendly materials. More importantly, traditional single-crosslinked structure hydrogels often have a rapid degradation rate or unstable structure during long-term wound repair, leading to a decline in functionality and an inability to sustainably and effectively support wound healing.
[0004] Document (A multifunctional hydrogel based on nature polysaccharide fabricated by Schiffbase reaction; DOI: 10.1016 / j.eurpolymj.2023.112330) discloses the preparation of a multifunctional hydrogel using carboxymethyl chitosan (CMCS) and oxidized hyaluronic acid (OHA); document (Status and future scope of plant-based green hydrogels in biomedical engineering; DOI: 10.1016 / j.apmt.2019.04.010) discloses the preparation of a hydrogel using a Schiff base reaction with plant-based materials; patent CN118384315A discloses the preparation of a composite hydrogel using dextran and sodium hyaluronate, which can be used for wound repair; the above technical solutions are difficult to simultaneously consider strength, stability and wound healing effect when preparing a hydrogel; moreover, some crosslinking agents are toxic and may cause environmental pollution problems; and the use of some crosslinking agents often requires complex reaction conditions, which is difficult to meet the demand for green, non-toxic and environmentally friendly materials. SUMMARY
[0005] [TECHNICAL PROBLEM]
[0006] When a conventional hydrogel is used for wound healing in diabetes, it is difficult to simultaneously consider strength, stability and wound healing effect.
[0007] [TECHNICAL SOLUTION]
[0008] To solve the above problems, the present application provides a double-crosslinked hydrogel based on E-PLMnO2 nanoscale enzyme and a preparation method and application thereof. Specifically, the present application uses guar gum and hyaluronic acid (HA) as the base material, and constructs a double-crosslinked three-dimensional network structure with excellent stability through the synergistic effect of borate ester bonds (chemical crosslinking) and hydrogen bonds (physical crosslinking); then introduces EM nanoscale enzyme composed of δ-MnO2 and ε-polylysine (EPL), which can effectively regulate the oxidative stress level in the wound microenvironment and inhibit bacterial infection.
[0009] The first object of the present application is to provide a method for preparing a double-crosslinked hydrogel based on E-PLMnO2 nanoscale enzyme, comprising the following steps:
[0010] The EM nanoscale enzyme is dispersed in water, guar gum (GG) and hyaluronic acid (HA) are sequentially added, and the mixture is uniformly mixed to form a mixed solution; the mixed solution is injected into a mold, borax solution is sprayed onto the surface thereof, and dynamic borate ester crosslinking is carried out by standing to obtain a double-crosslinked hydrogel based on E-PLMnO2 nanoscale enzyme.
[0011] In an embodiment of the present application, the concentration of EM nanoscale enzyme in the mixed solution is 0.01%-5%(w / v), preferably 0.1%(w / v), and w / v is g / 100mL.
[0012] In an embodiment of the present application, the concentration of guar gum (GG) in the mixed solution is 0.1%-5%(w / v), preferably 1.4%(w / v), and w / v is g / 100mL.
[0013] In an embodiment of the present application, the concentration of hyaluronic acid (HA) in the mixed solution is 0.1%-5%(w / v), preferably 0.6%(w / v), and w / v is g / 100mL.
[0014] In an embodiment of the present application, the mixing is uniform at 20-30°C (room temperature) and 300-800rpm for 1-3h.
[0015] In an embodiment of the present application, the borax solution is an aqueous borax solution with a concentration of 0.1%-10%(w / v), preferably 5%(w / v), and w / v is g / 100mL.
[0016] In an embodiment of the present application, the volume ratio of the mixed solution to the borax solution is 1:1-8:1; preferably 6:1.
[0017] In an embodiment of the present application, the standing is at 20-30°C (room temperature) for 20-60min.
[0018] In an embodiment of the present application, the preparation method of EM nanoscale enzyme is as follows:
[0019] Mixing tetramethylammonium hydroxide (TMAH) and a 3% mass concentration H2O2 solution uniformly to obtain a mixture of H2O2 and TMAH; wherein the ratio of the amount of tetramethylammonium hydroxide to the amount of H2O2 solution is 0.1-10g:1-100mL;
[0020] Adding a MnCl2 solution to the mixture of H2O2 and TMAH, stirring at 20-30°C (room temperature) and 500rpm for 12h, then centrifuging to collect the product, and then washing with anhydrous ethanol and deionized water for 3 times respectively to obtain δ-MnO2; wherein the mass ratio of MnCl2 to deionized water in the MnCl2 solution is 0.1-10g:20mL; and the ratio of the amount of the mixture of H2O2 and TMAH to the amount of the MnCl2 solution is 1g:1mL;
[0021] Dispersing 0.1g of δ-MnO2 in 100mL of deionized water, and ultrasonic treatment for 0.5-10h to make the δ-MnO2 decompose into a nanosheet solution;
[0022] 10 mL nanosheet solution and 10 mL of ε-polylysine (EPL) solution with a concentration of 20 mg / mL were mixed, ultrasonically treated for 10 min, centrifuged (7000 rpm, 5 min), washed with ethanol and deionized water for 3 times respectively, and dried to obtain EM nanoscale enzyme.
[0023] A second object of the present application is a double cross-linked hydrogel based on E-PLMnO2 nanoscale enzyme prepared by the method of the present application.
[0024] In an embodiment of the present application, the double cross-linked hydrogel based on E-PLMnO2 nanoscale enzyme can be injection molded, rapidly solidified and locally fitted.
[0025] A third object of the present application is the application of the double cross-linked hydrogel based on E-PLMnO2 nanoscale enzyme of the present application in the biomedical field.
[0026] In an embodiment of the present application, the application includes the preparation of wound repair materials, drug delivery materials, tissue filling materials, hemostatic materials, etc.
[0027] A fourth object of the present application is to provide a wound repair product containing the double cross-linked hydrogel based on E-PLMnO2 nanoscale enzyme of the present application.
[0028] A fifth object of the present application is to provide a chronic non-healing wound treatment drug containing the double cross-linked hydrogel based on E-PLMnO2 nanoscale enzyme of the present application.
[0029] A sixth object of the present application is a method for simultaneously improving the strength, stability and diabetic wound healing effect of a hydrogel, comprising the following steps:
[0030] The EM nanoscale enzyme is dispersed in water, guar gum (GG) and hyaluronic acid (HA) are sequentially added and mixed uniformly to form a mixed solution; the mixed solution is injected into a mold, borax solution is sprayed onto the surface thereof, and dynamic borate cross-linking is carried out by standing to obtain the double cross-linked hydrogel based on E-PLMnO2 nanoscale enzyme.
[0031] [Advantages]
[0032] The double cross-linked hydrogel based on E-PLMnO2 nanoscale enzyme of the present application belongs to a double cross-linked polysaccharide hydrogel material with structural innovation and functional integration, which overcomes the significant defects of traditional natural high molecular weight hydrogels in weak mechanical properties, poor stability and lack of multiple functions, and has a series of significant technical advantages and application potential.
[0033] Specifically:
[0034] (1) The application constructs a stable and dynamically adjustable double crosslinking network structure by introducing guar gum (GG) and hyaluronic acid (HA) into the same system and using borax to initiate the borate ester bond crosslinking between them, while superimposing the hydrogen bond interaction between GG and HA. This structure not only endows the hydrogel with excellent gelation ability and self-repairing performance, but also effectively improves its mechanical strength and structural integrity, ensuring the form maintenance and functional continuous exertion of the hydrogel in the wound environment.
[0035] (2) Compared with traditional materials relying on a single antibacterial component, the application innovatively introduces a biomimetic nanoenzyme complex EM (self-assembled from epsilon-polylysine and delta-MnO2 nanosheets), which integrates broad-spectrum antibacterial performance and active oxygen scavenging capacity. In the pathological wound microenvironment rich in free radicals, the nanoenzyme system can simulate the activity of natural antioxidant enzymes, efficiently scavenge excess ROS (such as H2O2, ABTS + and DPPH free radicals), thereby significantly alleviating oxidative stress, inhibiting inflammatory response, and effectively preventing cell apoptosis and tissue necrosis.
[0036] (3) Epsilon-polylysine itself has good biological safety and antibacterial spectrum coverage, and can synergistically exert a persistent antibacterial effect. In experiments on common pathogenic bacteria such as Staphylococcus aureus and Escherichia coli, it showed an antibacterial efficiency of more than 90%. Further, the hydrogel of the application can be injection molded, rapidly solidified, and locally adapted, suitable for on-site treatment of irregular wounds and postoperative wounds, while maintaining the microenvironment moisture and realizing structural support and function delivery.
[0037] (4) The GG / HA@EM hydrogel of the application significantly speeds up the wound closure in a diabetic wound model, promotes neovascularization and epithelial reconstruction, and achieves nearly complete healing of the wound on the 14th day, with a tissue repair level far superior to that of the untreated group and the blank hydrogel group, fully verifying the clinical translation potential of the hydrogel of the application in the treatment of chronic non-healing wounds.
[0038] In summary, through multi-level and multi-mechanism synergistic design, the application successfully solves the key technical bottlenecks in the prior art such as single function of hydrogel materials, unstable structure, and poor adaptability to complex wounds, and provides a new type of wound dressing with excellent mechanical properties, biological safety, antioxidant and antibacterial synergistic effect, which provides important technical support and material foundation for chronic wound treatment and intelligent wound care. BRIEF DESCRIPTION OF DRAWINGS
[0039] Figure 1 (a) is a preparation flow chart of GG / HA hydrogel (scale = 1 cm), and (b) is a typical photo of hydrogel (GG / HA3) after injection according to scheme 3.
[0040] Figure 2 SEM images of hydrogel of scheme 3 (GG / HA3) and scheme 1 (GG).
[0041] Figure 3 Swelling contrast images of GG / HA3 hydrogel 24 hours (scale bar = 1 cm) (a), 12 hours swelling ratio of different ratio hydrogels (n = 3) (b), degradation rate of GG / HA@EM at 37 °C of different ratio hydrogels (n = 3) (c).
[0042] Figure 4 Tensile stress-strain curves of different ratio hydrogels (a), quantitative analysis of tensile modulus (n = 3) (b), compressive stress-strain curves (c), quantitative analysis of compressive modulus (n = 3) (d).
[0043] Figure 5 Oscillatory sweep test (G' (a), G" (b)) and frequency sweep test (G' (c), G" (d)) of different ratio formulation hydrogels at 37 °C.
[0044] Figure 6 Injectability, skin adhesion and adhesion to different material objects of GG / HA@EM hydrogel macroscopic images (scale bar = 1 cm).
[0045] Figure 7 UV absorption peak determination of different concentrations of EM dispersion (a), standard regression curve and regression equation (b), calculated release amount according to regression equation (c), release situation on the first day and the third day (d).
[0046] Figure 8 Antioxidant performance test results of hydrogels of different concentrations of EM; wherein, (a) image of DPPH radical scavenging of GG / HA@EM of different EM concentrations for 1 hour (scale bar = 1 cm); (b) quantitative results of DPPH radical scavenging performance (n = 3); (c) image of ABTS radical scavenging of GG / HA@EM of different EM concentrations for 1 hour (scale bar = 1 cm); (d) quantitative results of ABTS radical scavenging performance (n = 3).
[0047] Figure 9 Cell compatibility test of GG / HA@EM-1 double crosslinked hydrogel; wherein, (a) is the test result of L929 cell live / dead staining (green fluorescence: calcein-AM represents live cells; red fluorescence: propidium iodide represents dead cells); (b) is the in vitro proliferation of fibroblasts measured by CCK-8 assay method (data is expressed as mean value; Ns, no statistical significance, **p < 0.01, *p < 0.05).
[0048] Figure 10 Antibacterial activity analysis of GG / HA@EM hydrogels with different EM contents; wherein a is antibacterial experiment; b and c are the statistics of the number of bacteria after S. aureus and E. coli were incubated at 37°C for 20h.
[0049] Figure 11 Wound healing test results of hydrogels with different concentrations of EM; wherein a is a representative image of wound healing and skin regeneration of mice treated with control and GG / HA@EM-1 at 1st, 3rd, 7th and 14th day; b is a schematic diagram of skin regeneration process within 14 days; c is quantitative data of relative wound healing percentage at different time points (n = 3).
[0050] Figure 12 H&E staining of regenerated tissues at 3rd, 7th, 14th day; double arrow: scar width; blue arrow: inflammatory cells (upper scale = 500 μm; lower scale = 50 μm).
[0051] Figure 13 H&E staining images of heart, liver, spleen, lung and kidney sections from rats at 14th day (scale = 50 μm); wherein a is the control group (natural healing after iodophor disinfection); b is the GG / HA@EM-1 treatment group.
[0052] Figure 14 CD31 immunofluorescence staining of wound regeneration area at 3rd, 7th, 14th day to evaluate angiogenesis (scale = 50 μm).DETAILED DESCRIPTION
[0053] The preferred embodiments of the present application are described below, and it should be understood that the embodiments are used to better explain the present application, and are not intended to limit the present application.
[0054] Test method:
[0055] 1. Swelling test:
[0056] To study the swelling properties of hydrogels, hydrogel samples were placed in molds to prepare cylindrical samples. Five groups of samples were prepared for control testing, and each group was measured three times. After the initial weight of the sample was measured, it was immersed in 5 mL of phosphate buffer solution (PBS, pH 7.4) and placed in a constant temperature shaker (37°C, 100 rpm) for incubation. To obtain accurate mass change data, the sample was taken out every certain time, the excess liquid on the surface was absorbed with filter paper, and then the weight was measured again. The swelling ratio (Swelling Ratio, SR) of the hydrogel was calculated according to the following formula:
[0057]
[0058] wherein W0and W t W0and W
[0059] 2. Stress-strain, tensile modulus, compressive stress-strain, compressive modulus tests:
[0060] The prepared hydrogels were molded into cylindrical samples with a diameter of about 10 mm and a height of about 10 mm. The samples were fixed on the testing platform and subjected to uniaxial compression tests at a compression speed of 1 mm / min at room temperature (25°C). The stress-strain data of the samples were recorded by the sensor to obtain their mechanical response characteristics. The deformation and structural changes of the hydrogels were monitored during the test to analyze their load-bearing capacity and compression deformation behavior.
[0061] 3. Degradation rate test:
[0062] Uniform-sized hydrogel samples were prepared, and the initial size and mass were recorded. The dry mass (W0) of each hydrogel sample was accurately weighed. Each dried gel sample was placed in a centrifuge tube or well plate containing 10 mL of PBS (pH 7.4), and the sample was placed in a 37°C constant-temperature incubator for incubation at rest or slow shaking. The sample was taken out at every set time point, and the surface moisture was gently absorbed with filter paper after the sample was taken out. The sample was vacuum dried to a constant weight, and the remaining mass W t was weighed.
[0063] The residual mass percentage was calculated using the following formula:
[0064]
[0065] 4. Rheological test:
[0066] All experiments were conducted at 25°C.
[0067] First, the oscillation amplitude characteristics of the hydrogel were tested. In this experiment, the fixed angular frequency was 10 rad·s -1 , and the strain range was adjusted (0.1%-100%) to study the strain dependence and viscoelastic characteristics of the hydrogel. Next, the oscillation frequency characteristics test was conducted. Under a strain condition of 0.1%, the angular frequency range of the hydrogel was 100 rad·s -1 to 0.1 rad·s -1 . In addition, a time rheological experiment was conducted to measure the rheological changes of the hydrogel within 120 seconds to evaluate its stability and recoverability under the action of time. Finally, in order to study the effect of temperature on the rheological behavior of the hydrogel, a series of temperature rheological experiments were conducted. The rheological properties of the hydrogel were tested in the temperature range of 30°C to 60°C to analyze the viscoelastic changes and thermal stability of the hydrogel under different temperature conditions.
[0068] 5. Antioxidant capacity test:
[0069] (1) DPPH radical scavenging capacity test:
[0070] First, DPPH solution was prepared with a concentration of 0.1 mM dissolved in ethanol and stored at room temperature in the dark. Then, 1 g of hydrogel sample with different EM content was mixed with 5 mL of prepared DPPH solution and reacted in the dark for 30 minutes. After the reaction, the absorbance of the solution was measured by UV-Vis spectrophotometer (UV-Vis, λ = 517 nm). The formula for calculating the scavenging rate of DPPH radicals by the sample is as follows:
[0071]
[0072] where A sample is the absorbance of the hydrogel sample group, and A control is the absorbance of pure DPPH solution.
[0073] (2) ABTS radical scavenging capacity test
[0074] ABTS·+ radical solution was prepared by reacting ABTS with hydrogen peroxide. 5 mg of ABTS solid powder was dissolved in an appropriate amount of deionized water to prepare a 10 mM ABTS stock solution, which was stored in the dark. When used, 10 mL of ABTS stock solution was taken; about 50 μL of hydrogen peroxide solution (concentration of 30%) was added; the mixture was gently stirred and placed at room temperature for 30 minutes to generate ABTS·+ radicals. Then, 1 g of hydrogel sample was mixed with 5 mL of ABTS·+ radical solution and reacted at room temperature for 30 minutes. UV-Vis (λ = 734 nm) was used to measure the change in absorbance. The formula for calculating the radical scavenging rate is the same as that for DPPH.
[0075] 6. Adhesion performance test:
[0076] Different materials such as pigskin, stainless steel, glass, polytetrafluoroethylene, plastic, and polypropylene were selected to be placed together with the hydrogel and inverted to observe the adhesion between them.
[0077] 7. Antimicrobial activity test:
[0078] To evaluate the antimicrobial effect of the prepared hydrogel, plate coating method was used to culture and count colonies of gram-negative E. coli and gram-positive S. aureus.
[0079] (1) Preparation of LB medium
[0080] Luria-Bertani (LB) liquid medium was prepared as follows:
[0081] Dissolve 10 g of tryptone, 5 g of yeast extract, and 10 g of sodium chloride in 1 L of distilled water, and adjust the pH to 7.0 ± 0.2. The prepared medium was sterilized by autoclaving (121 °C, 20 min) to remove the bacteria, and was ready for use. The LB solid medium was prepared by adding 15 g / L of agar powder to the above liquid formulation, and was sterilized by autoclaving and poured into Petri plates in a clean bench.
[0082] (2) Bacterial culture
[0083] First, 20 μL of E. coli and S. aureus bacterial solution was taken and added to 20 mL of LB liquid medium, respectively, and incubated at 37 °C for 12 hours until the bacteria reached the logarithmic growth phase. The optical density of the culture solution was monitored using a spectrophotometer (OD600) to ensure that the concentration of the bacterial suspension was suitable for subsequent experiments. When the bacteria grew to the logarithmic growth phase, the concentration of the bacterial suspension was adjusted to an OD value of 0.1, which was equivalent to a bacterial concentration of about 1 x 10 6 CFU / mL.
[0084] (3) Plate spreading method test
[0085] The hydrogel sample (1 mL) was mixed with the prepared bacterial suspension (concentration of 1 x 10 6 CFU / mL) at a ratio of 1:1, and gently shaken for 10 minutes to ensure uniform mixing of the bacteria and the hydrogel. Then, 50 μL of the mixed liquid was spread on the surface of the LB solid medium plate. The coated LB plate was sealed and incubated in a biochemical incubator at 37 °C for 20 hours to ensure that the bacteria grew on the medium and formed countable colonies. Then the number of viable bacterial colonies was calculated. The bacterial survival rate (%) was calculated using the formula:
[0086]
[0087] CFUexpis the number of colonies in the experimental group, and CFUconis the number of colonies in the control group without hydrogel.
[0088] 8. Wound healing test:
[0089] Two 1 cm circular full-thickness skin wounds were created on the back of the rats to evaluate the ability of the hydrogel to promote wound healing. After the wounds were preliminarily sterilized with 10% ketamine anesthesia, the hydrogel was evenly applied to the wound area of the sample group. A transparent sterile dressing was applied for observation, and a tape was used for fixation.
[0090] Wound healing was assessed by measuring wound area, observing wound contraction, and performing histological analysis under a microscope. The healing process, including wound healing rate and tissue repair status, was monitored on days 1, 3, 7, and 14 after wounding. Tissue samples were collected for histological examination (H&E staining). Data were analyzed using SPSS software. Intergroup comparisons were performed by one-way analysis of variance, and p values < 0.05 were considered statistically significant.
[0091] (1) HE staining
[0092] Rat wound tissue samples were fixed in 10% neutral formalin for 24 hours and then subjected to routine processing, including dehydration, transparency, and embedding. Samples were cut into 5-μm-thick sections using a microtome and mounted on glass slides. HE staining was then performed to observe changes in tissue structure during wound healing. Morphological changes in the wound tissue of each group were observed under a microscope, and representative images were taken to assess wound repair efficacy.
[0093] (2) CD31 fluorescence staining
[0094] To further investigate the angiogenesis process, CD31 fluorescent staining was performed on wound sections. CD31 (also known as PECAM-1) is a marker molecule for endothelial cells, and its fluorescent staining clearly identifies new blood vessels in the wound area. After antigen retrieval and blocking of nonspecific binding sites, sections were incubated with a CD31 antibody as the primary antibody, followed by staining with a fluorescently labeled secondary antibody. After staining, angiogenesis was observed using a fluorescence microscope.
[0095] 9. In vitro proliferation of fibroblasts:
[0096] (1) Cell culture
[0097] Mouse fibroblasts (L929) were cultured and passaged in standard culture medium at 37°C, 95% air and 5% CO2. The third generation L929 cells were cultured at 1.0×10 4 Cells were seeded in 96-well plates at an initial concentration of 10 cells / well and cultured overnight at 37°C. The different sample components were added to standard culture medium, and extracts were prepared in a 37°C incubator. Subsequently, 10 μL of each extract was added to the wells and incubated with the cells for 48 hours. Cell viability was then assessed using a CCK-8 assay kit.
[0098] (2) Cell proliferation assay
[0099] To further evaluate cell proliferation in vitro, L929 cells were plated at 5.0 × 10 3The initial concentration of cells per well was inoculated in a 24-well plate and incubated at 37°C overnight. Then, 1 mL of each extract (extract after 3 days of co-culture of hydrogel and medium) was added to the wells, and the cells were co-cultured for 24, 48 and 72 hours, and the plates were removed at each time point. Then, cell viability was evaluated using the LIVE / DEAD assay kit, and the results were observed and recorded using a fluorescence microscope. Green fluorescence indicates live cells, while red fluorescence indicates dead cells.
[0100] Raw materials used in the examples:
[0101] Guar gum: 99.9%, Shanghai Maikelin Reagent Co., Ltd.;
[0102] Hyaluronic acid: analytical pure, Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0103] Borax: analytical pure, Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0104] Water: deionized water;
[0105] The preparation method of EM nanoscale enzyme is as follows:
[0106] Mix 5 g of tetramethylammonium hydroxide (TMAH) and 40 mL of 3% mass concentration H2O2 solution uniformly to obtain a mixture of H2O2 and TMAH;
[0107] Add 20 mL of MnCl2 solution to 20 g of the mixture of H2O2 and TMAH, stir at room temperature and 500 rpm for 12 h, then centrifuge to collect the product, and then wash it with anhydrous ethanol and deionized water for 3 times respectively to obtain δ-MnO2; wherein the mass ratio of MnCl2 in the MnCl2 solution to deionized water is 1 g: 20 mL;
[0108] Disperse 0.1 g of δ-MnO2 in 100 mL of deionized water, and ultrasonic treat for 0.5-10 h to make δ-MnO2 decompose into a nanosheet solution;
[0109] Mix 10 mL of the nanosheet solution with 10 mL of ε-polylysine (EPL) solution with a concentration of 20 mg / mL, ultrasonic treat for 10 min, centrifuge (7000 rpm, 5 min), wash with ethanol and deionized water for 3 times respectively, and dry to obtain EM nanoscale enzyme.
[0110] Room temperature refers to 20-30°C.
[0111] The solutions involved in the examples and comparative examples are water as the solvent if the solvent is not specified; w / v is g / 100 mL.
[0112] Example 1 Screening of GG / HA hydrogel
[0113] Scheme 1:
[0114] Guar gum and water were mixed, stirred at 500 rpm for 2 h at room temperature to obtain a guar gum solution with a concentration of 2% (w / v); then 3 mL of the guar gum solution was injected into a mold (cylindrical recess with a diameter of 2 cm and a height of 1 cm), 0.5 mL of a borate solution with a concentration of 5% (w / v) was sprayed onto the surface thereof, and dynamic borate ester crosslinking was carried out at room temperature for 30 min to obtain a hydrogel (GG).
[0115] Scheme 2:
[0116] Guar gum, hyaluronic acid and water were mixed, stirred at 500 rpm for 2 h at room temperature to obtain a mixed solution with a guar gum concentration of 1.6% (w / v) and a hyaluronic acid concentration of 0.4%; then 3 mL of the mixed solution was injected into a mold (cylindrical recess with a diameter of 2 cm and a height of 1 cm), 0.5 mL of a borate solution with a concentration of 5% (w / v) was sprayed onto the surface thereof, and dynamic borate ester crosslinking was carried out at room temperature for 30 min to obtain a hydrogel (GG / HA = 8:2, GG / HA2).
[0117] Scheme 3:
[0118] Guar gum, hyaluronic acid and water were mixed, stirred at 500 rpm for 2 h at room temperature to obtain a mixed solution with a guar gum concentration of 1.4% (w / v) and a hyaluronic acid concentration of 0.6%; then 3 mL of the mixed solution was injected into a mold (cylindrical recess with a diameter of 2 cm and a height of 1 cm), 0.5 mL of a borate solution with a concentration of 5% (w / v) was sprayed onto the surface thereof, and dynamic borate ester crosslinking was carried out at room temperature for 30 min to obtain a hydrogel (GG / HA = 7:3, GG / HA3).
[0119] Scheme 4:
[0120] Guar gum, hyaluronic acid and water were mixed, stirred at 500 rpm for 2 h at room temperature to obtain a mixed solution with a guar gum concentration of 1.2% (w / v) and a hyaluronic acid concentration of 0.8%; then 3 mL of the mixed solution was injected into a mold (cylindrical recess with a diameter of 2 cm and a height of 1 cm), 0.5 mL of a borate solution with a concentration of 5% (w / v) was sprayed onto the surface thereof, and dynamic borate ester crosslinking was carried out at room temperature for 30 min to obtain a hydrogel (GG / HA = 6:4, GG / HA4).
[0121] Example 2
[0122] A method for preparing a double-crosslinked hydrogel based on E-PLMnO2 nanozyme, comprising the following steps:
[0123] EM nanozyme was dispersed in water to obtain an EM nanozyme dispersion with a concentration of 0.2% (w / v);
[0124] Guar gum (GG) and hyaluronic acid (HA) were sequentially added to the EM nanozyme dispersion, and stirred at room temperature and 500 rpm for 2 h to form a mixed solution; wherein the concentration of guar gum (GG) in the mixed solution was 1.4% (w / v); the concentration of hyaluronic acid (HA) was 0.6% (w / v);
[0125] Then, 3 mL of the mixed solution was injected into a mold (a cylindrical groove with a diameter of 2 cm and a height of 1 cm), and 0.5 mL of a 5% (w / v) borax solution was sprayed on its surface. The mixture was allowed to stand at room temperature for 30 minutes for dynamic borate cross-linking to obtain a double-cross-linked hydrogel (GG / HA@EM) based on E-PLMnO2 nanozyme.
[0126] The obtained hydrogel was subjected to performance testing, and the test results are as follows:
[0127] Figure 1 The preparation flow chart of GG / HA hydrogel (scale bar = 1 cm) (a), and the typical photo of the hydrogel of scheme 3 (GG / HA3) after injection (b). Figure 1 It can be seen that the surface of the hydrogel is smooth, reflecting its excellent rapid self-repair ability.
[0128] Figure 2 The SEM images of the hydrogel (GG / HA3) of Scheme 3 and the hydrogel (GG) of Scheme 1 are shown in FIG. Figure 2 It can be seen that compared with the loose structure and larger pore size of pure GG cross-linked hydrogel, the GG / HA3 dual-cross-linked hydrogel exhibits a denser and stronger three-dimensional network structure. This structure has a smaller pore size and higher density, showing excellent structural stability and compressive resistance. Its dense network structure effectively reduces bacterial penetration, providing a stronger physical barrier. Compared with loose and easily degradable networks, it can slowly release drugs over a longer period of time, providing more lasting therapeutic effects. The introduction of HA significantly enhances the cross-linking density of the GG hydrogel, forming a more compact and robust interpenetrating network structure.
[0129] Figure 3 Comparative images of GG / HA3 hydrogel swelling after 24 hours (scale bar = 1 cm) (a), swelling rate of hydrogels with different ratios after 12 hours (n = 3) (b), degradation rate of GG / HA@EM with different ratios at 37°C (n = 3) (c). Figure 3It can be seen that the hydrogel of GG / HA3 has good swelling performance, which may help to absorb the exudate at the wound site; compared with the GG hydrogel with single chemical cross-linking, the swelling rate of the double-cross-linked hydrogel shows a decreasing trend, among which the GG / HA=7:3(GG / HA3) group decreases by about 10%. Through the degradation test for one week in a 37℃ environment, it can be seen that the double-cross-linked hydrogel has a longer degradation period, among which GG / HA3 and GG / HA@EM are completely degraded after 7 days.
[0130] Figure 4 The tensile stress-strain curves (a), quantitative analysis of tensile modulus (n=3) (b), compression stress-strain curves (c), quantitative analysis of compression modulus (n=3) (d) of hydrogels with different proportions are shown in FIG. 6. From Figure 4 It can be seen that the tensile modulus of GG, GG / HA2, GG / HA3, GG / HA4, and GG / HA@EM hydrogels is 4.98 KPa, 6.61 KPa, 7.95 KPa, 5.29 KPa, and 5.65 KPa; the tensile modulus of the double-cross-linked hydrogel increases significantly from 4.98 KPa to 7.95 KPa, among which the tensile modulus of the GG / HA@EM hydrogel is twice that of the GG hydrogel. The compression modulus of GG, GG / HA2, GG / HA3, GG / HA4, and GG / HA@EM hydrogels is 8.67 KPa, 20.68 KPa, 24.37 KPa, 12.82 KPa, and 16.18 KPa; the compression modulus of the GG / HA@EM hydrogel is 3 times that of the GG hydrogel.
[0131] Figure 5 The oscillation scanning test (G'(a), G"(b)) and frequency scanning test (G'(c), G"(d)) of hydrogels with different proportions were carried out at 37℃. From Figure 5It can be seen that in the range of increasing frequency from 0.1 Hz to 20 Hz, the storage modulus (G') of all hydrogels is significantly higher than the loss modulus (G"), which reveals the long-term structural stability of GG / HA@EM hydrogel as an elastomer. At 1 Hz and 37℃, the average G' value of GG / HA2, GG / HA3, GG / HA4, and GG / HA@EM double-crosslinked hydrogels is about twice that of single-crosslinked GG hydrogel, further confirming the significant enhancement of double-crosslinking strategy on the mechanical properties of hydrogel. GG / HA@EM hydrogel shows the highest average G' value in all tested frequency ranges, which is about three times that of the original GG hydrogel. This significant improvement in mechanical properties can be attributed to the increase in crosslinking density in the double-crosslinked network, resulting in a more compact and stable network structure. The consistency of rheological test results and elasticity test results further indicates that the double-crosslinking strategy not only significantly enhances the mechanical strength of the hydrogel, but also provides a strong guarantee for its robustness in practical applications.
[0132] Figure 6 Macroscopic images of the injectability, skin adhesion, and adhesion to different material objects of GG / HA@EM hydrogel (scale = 1 cm). From left to right: a) injection of GG / HA@EM hydrogel into a syringe; b) injection of GG / HA@EM hydrogel into a mouse skin; c) adhesion of GG / HA@EM hydrogel to a glass slide; d) adhesion of GG / HA@EM hydrogel to a plastic film; e) adhesion of GG / HA@EM hydrogel to a metal plate. Figure 6 It can be seen that: GG / HA@EM hydrogel can maintain structural integrity after experiencing these mechanical deformations, and closely adhere to the skin surface, indicating that it has excellent tissue adhesion ability and mechanical adaptability. This performance enables it to effectively adapt to the dynamic changes of the skin, thereby providing stable protection and support during the wound healing process.
[0133] Example 3
[0134] Adjust the concentration of EM nanoscale enzyme in the mixture of Example 2 to 0, 0.5, 1, 2 mg / mL, and keep the rest the same as Example 2, to obtain hydrogels, marked as GG / HA, GG / HA@EM-0.5, GG / HA@EM-1, GG / HA@EM-2 (GG / HA@EM of Example 2).
[0135] Adjust the concentration of EM nanoscale enzyme in the mixture of Example 2 to 1 mg / mL, and omit HA, and keep the rest the same as Example 2, to obtain hydrogel GG@EM-1.
[0136] The obtained hydrogels were tested for performance, and the test results are as follows:
[0137] Figure 7 UV absorption peak determination (a), standard regression curve and regression equation (b), calculated release amount according to the regression line equation (c), release situation on the first day and the third day (d) for EM dispersions of different concentrations. From left to right: a) UV absorption peak determination of EM dispersions of different concentrations; b) standard regression curve and regression equation; c) calculated release amount according to the regression line equation; d) release situation on the first day and the third day. Figure 7It can be seen that: the GG / HA double cross-linked hydrogel presents a slower release rate than the single cross-linked hydrogel GG. Under the condition of both loaded with 1 mg / ml EM, the single cross-linked hydrogel reaches 100% release at 5 days, while the double cross-linked hydrogel reaches 100% release at 8 days. Such results are more conducive to achieving precise treatment according to different biological needs of wound healing. The release process of EM presents a layered release mode, which is highly consistent with the process of granulation tissue formation and epithelialization in the process of skin wound healing, which usually progresses gradually from the periphery to the center of the wound. This process of staged release ensures that the delivery of EM accurately corresponds to different stages of wound healing, thereby effectively improving the therapeutic effect. Specifically, the outer layer of the hydrogel begins to degrade first and releases EM to the surface area of the wound, and then the inner layer gradually degrades and releases more EM, ensuring that the drug can continuously and uniformly play a role throughout the wound healing process.
[0138] Figure 8 The results of the antioxidant performance test of hydrogels with different concentrations of EM; wherein (a) image of DPPH radical scavenging by GG / HA@EM with different EM concentrations for 1 hour (scale = 1 cm); (b) quantitative results of DPPH scavenging performance (n = 3); (c) image of ABTS radical scavenging by GG / HA@EM with different EM concentrations for 1 hour (scale = 1 cm); (d) quantitative results of ABTS scavenging performance (n = 3). From Figure 8 It can be seen that: after adding the hydrogel, the color of the radical-loaded solution becomes significantly lighter, which intuitively reflects the radical scavenging effect of the hydrogel. Quantitative analysis results show that after 1 h, the DPPH and ABTS scavenging rates of GG / HA@EM-2 are the highest, reaching 83.86% and 98.98% respectively, the scavenging rates of GG / HA@EM-1 are 69.8% and 74.8%, the scavenging rates of GG / HA@EM-0.5 are 38.99% and 51.41%, and the scavenging rates of single cross-linked hydrogel GG are only 16.62% and 8.98%. Compared with the control group (GG@EM-1), the GG / HA@EM hydrogel can neutralize more than 80% of the radicals, indicating that it has significant antioxidant capacity. This performance enables it to effectively regulate oxidative stress in the microenvironment of wound healing, thereby creating favorable conditions for tissue repair in the inflammatory stage.
[0139] Figure 9Cell compatibility test of GG / HA@EM-1 double cross-linked hydrogel; wherein, the test results of L929 cell live / dead staining (green fluorescence: calcein-AM represents live cells; red fluorescence: propidium iodide represents dead cells) (a), in vitro proliferation of fibroblasts measured by CCK-8 assay (data expressed as mean value; Ns, not statistically significant, **p<0.01, *p<0.05) (b). From Figure 9 It can be seen that: after co-culturing with GG / HA@EM-0.5, GG / HA@EM-1, GG / HA@EM-2 hydrogel for 3 days, the survival rate and proliferation of L929 cells have no significant difference compared with the control group (natural growth), and no obvious cell death phenomenon is observed. Day 1 is 100% as the starting value; Day 2 cell proliferation to 187%-190%, no significant difference, NS; Day 3 cell proliferation to 316%-321%, also no significant difference, NS. The live / dead staining results further confirm that the cell morphology on and around the hydrogel surface is normal, and no typical characteristics of apoptosis or necrosis are observed.
[0140] Figure 10 Antibacterial activity analysis of GG / HA@EM hydrogel with different EM contents; wherein, a is the antibacterial experiment; b and c are the statistics of the number of bacteria after S. aureus and E. coli are incubated at 37°C for 20h. Single factor ANOVA is used to analyze the difference, and Tukey post-hoc test is used for pairwise comparison. Data expressed as mean value; Ns, not statistically significant, **p<0.01, *p<0.05. From Figure 10 It can be seen that: after co-culturing GG / HA@EM hydrogel with bacteria solution with OD value of 0.1 for 3 hours, spreading on LB agar plate and incubating at 37°C for 20 hours. The experimental results show that the hydrogel group (EM-0.5~EM-2.0) shows significant antibacterial effect on the two kinds of bacteria, and the antibacterial effect increases with the increase of EM concentration, showing obvious concentration dependence.
[0141] Figure 11 Wound healing test results of hydrogel with different concentrations of EM; wherein, a is a representative image of wound healing and skin regeneration of control group (iodine after disinfection, natural healing), GG / HA@EM-1 treated mice at 1st, 3rd, 7th and 14th day; b is a schematic diagram of skin regeneration process within 14 days; c is the quantitative data of relative wound healing percentage at different time points (n=3). Data expressed as mean value; Ns, not statistically significant, **p<0.01, *p<0.05. Figure 11It can be seen that: by day 3, the GG / HA@EM treatment group has shown a clear wound healing trend, while the control group (natural healing after iodophor disinfection) progresses slowly. By day 7, although the wounds in both groups are not completely healed, the wound healing rate of the GG / HA@EM group is about 34.4% faster than the control group, indicating that the GG / HA@EM hydrogel can significantly accelerate wound repair. This effect may be closely related to the multiple functions of the hydrogel, such as antioxidant, antibacterial, and improvement of the local microenvironment. It is worth noting that by day 14, the wound healing rate of the GG / HA@EM group reached 94.72%, almost completely healed, while the closure rate of the control group was significantly lower. This result further verifies the significant advantage of GG / HA@EM hydrogel in promoting diabetic wound healing. Its excellent performance may be attributed to the multifunctional properties of the hydrogel, including ROS scavenging capacity, continuous oxygen supply, and good biocompatibility, which together create a favorable microenvironment for wound repair.
[0142] Figure 12 For H&E staining of regenerated tissues on day 3, 7, 14; double arrow: scar width; blue arrow: inflammatory cells (upper scale = 500 pm; lower scale = 50 pm). From Figure 12 It can be seen that: the control group (natural healing after iodophor disinfection) shows a wide scar tissue in the wound area, accompanied by a large number of inflammatory cell infiltration (indicated by blue arrows), indicating that the control group (natural healing after iodophor disinfection) has a persistent inflammatory response and tissue repair disorder during wound healing. In contrast, the scar width of the GG / HA@EM-1 treatment group is significantly reduced, and the inflammatory cell infiltration is significantly reduced, showing a more orderly tissue regeneration process. This significant improvement may be attributed to the multiple functional properties of EM, which effectively neutralizes the excess ROS at the wound site, reducing the damage to cells by oxidative stress; at the same time, its antibacterial properties inhibit bacterial infection, thereby reducing the persistent occurrence of inflammatory response. In addition, the mechanical properties and moisturizing capacity of GG / HA@EM hydrogel may further provide a suitable microenvironment for cell migration and proliferation, promoting rapid repair of tissues.
[0143] Figure 13 H&E staining images of heart, liver, spleen, lung and kidney sections from day 14 rats (scale = 50 pm). After 14 days of treatment, tissue samples of key organs such as heart, liver, spleen, lung and kidney were collected and subjected to pathological analysis by H&E staining. From Figure 13The GG / HA@EM-1-treated group showed no abnormal changes in the main organ tissue structure compared to the control group (which healed naturally after iodine disinfection). Cell morphology, tissue arrangement, and vascular distribution remained normal. This result demonstrates that the GG / HA@EM-1 hydrogel did not cause systemic toxicity at the experimental dose and exhibits good biocompatibility and safety.
[0144] Figure 14 CD31 immunofluorescence staining was performed on the wound regeneration area on days 3, 7, and 14 to evaluate angiogenesis. (Scale bar = 50 μm). Figure 14 It can be seen that compared with the blank control group (natural healing after iodine disinfection), the CD31 expression level in the wound tissue of the GG / HA@EM-1 hydrogel-treated group increased significantly, indicating that the hydrogel can effectively promote the formation of new blood vessels. This pro-angiogenic effect may be mainly attributed to the double-cross-linked network design of the GG / HA@EM-1 hydrogel, which achieves the sustained release of HA through the synergistic effect of physical cross-linking and chemical cross-linking, thereby maintaining a high local concentration at the wound site. The antioxidant properties of the GG / HA@EM-1 hydrogel reduce the damage of oxidative stress to vascular endothelial cells by clearing excessive ROS, further optimizing the microenvironment for angiogenesis. It is worth noting that the mechanical properties and moisturizing ability of the GG / HA@EM-1 hydrogel also provide suitable physical support for cell migration and angiogenesis, thereby accelerating the wound healing process.
[0145] Example 4
[0146] The concentrations of the borax solution in Example 2 were adjusted to 1, 3, and 10% (w / v), while the other conditions remained the same as in Example 2 to obtain a hydrogel.
[0147] The obtained hydrogel was subjected to performance testing, and the test results are as follows:
[0148] When the borax concentration is 1%, its tensile modulus is 3.5KPa and its compression modulus is 6.0KPa. This may be because when the borax concentration is low, the dynamic cross-linking is insufficient, the structure is loose, the hydrogel is softer but the overall strength is weaker.
[0149] When the borax concentration is 3%, its tensile modulus is 5.1KPa, the compression modulus is 12.2KPa, the cross-linking strength is moderate, and the mechanical properties are close to those of the sample with 5%.
[0150] When the borax concentration is 10%, its tensile modulus is 4.8KPa and its compression modulus is 14.3KPa. Borax with a higher concentration is not easy to dissolve completely, forming microcrystals, which reduces the actual effective cross-linking density.
[0151] Comparative Example 1
[0152] Adjustment of guar gum in Example 2 to xanthan gum, other and Example 2 consistent, get hydrogel.
[0153] The performance test of the hydrogel obtained by the comparative example is as follows:
[0154] Due to the high carboxyl content of xanthan gum, the crosslinking efficiency of borax is low, and the mechanical strength is greatly reduced. The compression modulus of the obtained hydrogel is only 0.246KPa.
[0155] Comparative Example 2
[0156] Adjustment of guar gum in Example 2 to gellan gum, other and Example 2 consistent, get hydrogel.
[0157] The performance test of the hydrogel obtained by the comparative example is as follows:
[0158] Gellan gum is easy to form a rigid network, high strength but strong brittleness, the obtained hydrogel cannot be soft and fit the wound, the tensile strain is only 0.16%, and the hydrogel is broken when the tensile limit is exceeded. In addition, the grid of gellan gum is dense, and the release rate of EM loaded is very low, only 14% after 7 days, which cannot achieve the purpose of antibacterial and antioxidant.
[0159] Comparative Example 3
[0160] Adjustment of hyaluronic acid in Example 2 to chitosan, other and Example 2 consistent, get hydrogel.
[0161] The performance test of the hydrogel obtained by the comparative example is as follows:
[0162] Chitosan lacks vicinal diol groups, and the self-healing performance of the obtained hydrogel is greatly reduced. At the same time, the replacement of chitosan cannot promote vascular activity and accelerate vascular regeneration.
[0163] Comparative Example 4
[0164] Adjustment of borax in Example 2 to glutaraldehyde, other and Example 2 consistent, get hydrogel.
[0165] The performance test of the hydrogel obtained by the comparative example is as follows:
[0166] The obtained glutaraldehyde hydrogel has high modulus, the tensile modulus reaches 16.45KPa, and the compression modulus is 32.15KPa, but the residual glutaraldehyde in the hydrogel has strong toxicity. In the results of L929 cell proliferation, the cell death rate is high and the survival rate is low, and the survival rate is only 1.65% after 3 days of culture
[0167] Comparative Example 5
[0168] A method for preparing a double-crosslinked hydrogel based on E-PLMnO2 nanoszyme, comprising the following steps:
[0169] Mixing EM nanoszyme, guar gum (GG), hyaluronic acid (HA) and water, stirring at room temperature and 500 rpm for 2 h to form a mixed solution;
[0170] Then, 3 mL of the mixed solution is injected into a mold (cylindrical recess with a diameter of 2 cm and a height of 1 cm), 0.5 mL of a borax solution with a concentration of 5% (w / v) is sprayed onto the surface of the mold, and dynamic borate crosslinking is carried out at room temperature for 30 min;
[0171] The specific parameters remain the same as in Example 2; and the hydrogel is obtained.
[0172] The hydrogel obtained in the comparative example is subjected to performance testing, and the test results are as follows:
[0173] The EM nanoszyme is not dispersed in advance, and the EM nanoszyme will agglomerate to form stress defects in the hydrogel; and the overall performance of the hydrogel is greatly reduced, and the agglomerated EM cannot be released smoothly.
[0174] Comparative Example 6
[0175] The GG in Example 2 is omitted, and the other parameters remain the same as in Example 2; and the hydrogel is obtained.
[0176] The hydrogel obtained in the comparative example is subjected to performance testing, and the test results are as follows:
[0177] The pure HA cannot form a hydrogel under the same conditions, and remains in a liquid state, and cannot be subjected to relevant tests.
[0178] Comparative Example 7
[0179] The EM in Example 2 is replaced by silver nanoparticles, and the other parameters remain the same as in Example 2; and the hydrogel is obtained.
[0180] The hydrogel obtained in the comparative example is subjected to performance testing, and the test results are as follows:
[0181] The GG / HA hydrogel loaded with silver nanoparticles has a too fast release rate, and the release rate of the silver nanoparticles reaches 100% after 2 h, without a sustained release effect.
[0182] Although the present application has been disclosed with reference to the preferred embodiments above, it is not intended to limit the present application, and any person skilled in the art can make various modifications and modifications without departing from the spirit and scope of the present application, and therefore the protection scope of the present application should be defined by the claims.
Claims
1. A method for preparing a double-crosslinked hydrogel based on E-PLMnO2 nanozyme, characterized in that: The steps include: EM nanozyme was dispersed in water, and guar gum (GG) and hyaluronic acid (HA) were added in sequence and mixed evenly to form a mixed solution; the mixed solution was injected into a mold, borax solution was sprayed on its surface, and the mold was allowed to stand for dynamic borate cross-linking to obtain a double-cross-linked hydrogel based on E-PLMnO2 nanozyme.
2. The method according to claim 1, characterized in that The concentration of EM nanozyme in the mixed solution is 0.01%-5% (w / v); the concentration of guar gum (GG) is 0.1%-5% (w / v); and the concentration of hyaluronic acid (HA) is 0.1%-5% (w / v).
3. The method according to claim 1, characterized in that The borax solution is an aqueous solution of borax with a concentration of 0.1% (w / v) to 10% (w / v).
4. The method according to claim 1, wherein The volume ratio of the mixed solution to the borax solution is 1:1-8:
1.
5. A double-cross-linked hydrogel based on E-PLMnO2 nanozyme prepared by the method according to any one of claims 1 to 4.
6. Application of the double-crosslinked hydrogel based on E-PLMnO2 nanozyme according to claim 5 in the biomedical field.
7. The use according to claim 6, characterized in that Applications include the preparation of wound repair materials, drug delivery materials, tissue filling materials, hemostatic materials, etc.
8. A wound repair product, characterized in that: Contains the double-cross-linked hydrogel based on E-PLMnO2 nanozyme as described in claim 5.
9. A drug for treating chronic, difficult-to-heal wounds, characterized in that: Contains the double-cross-linked hydrogel based on E-PLMnO2 nanozyme as described in claim 5.
10. A method for simultaneously improving the strength, stability and diabetic wound healing effect of a hydrogel, characterized in that: The steps include: EM nanozyme was dispersed in water, and guar gum (GG) and hyaluronic acid (HA) were added in sequence and mixed evenly to form a mixed solution; the mixed solution was injected into a mold, borax solution was sprayed on its surface, and the mold was allowed to stand for dynamic borate cross-linking to obtain a double-cross-linked hydrogel based on E-PLMnO2 nanozyme.
Citation Information
Patent Citations
Antibacterial and antioxidant hydrogel dressing for treating diabetic wounds and preparation method thereof
CN114984299A
Preparation method of injectable hydrogel dressing containing self-assembled activated nano-enzyme as well as product and application of injectable hydrogel dressing
CN117919486A
Guar gum hydrogel with biological activity as well as preparation method and application of guar gum hydrogel
CN119656367A
Borated polysaccharide absorbents and absorbent products
US4624868A
Antibacterial, antioxidant hydrogel dressing for treating diabetic wounds and preparation method therefor
WO2023231051A1